Órtese de tornozelo: efeito sobre variáveis dinamométricas e eletromiográficas durante exercício em intensidade do jogo basquetebol - Castro, Alex [UNESP] (2014)
The aim of the present study was to investigate the effects of the use of ankle brace and fatigue on peak torque and muscle activation of ankle stabilizer muscles, and on ground force reaction (GFR) in vertical jumps, during a simulation of the basketball game (SBG). Eleven male basketball players (age: 17.1 ± 0.1 years old; height: 183.3 ± 8.7 cm; body mass: 75.6 ± 9.0 kg) performed a SBG in the laboratory under two conditions: with and without ankle bracing. The test was composed of a succession of intermittent physical effort (running, side shuffle, changes in direction and jumps) equally distributed in four periods of 10 min each, with duration and intensity similar to basketball game. Prior to the test, at the half-time interval and after the test, the participants performed five maximal isokinetic concentric-eccentric contractions of ankle invertors and evertors muscles, at 60°.s-1 and 120°.s-1. In these evaluations, was collected inverter and evertor peak torque and electromyoghaphic activity of the tibialis anterior, peroneus longus and peroneus brevis muscles. During the test were measured vertical and mediolateral GRF during the jumps did in each period. The variables were analyzed statistically by repeated measures ANOVA with four factors (condition, velocity, type of contraction and isokinetic evaluation) for peak torque and muscle activation, and two factors (condition and period) for the GFR. The significance level was set at α 5%. The results showed that the fatigue induced by SBG decreased evertor (-5% at -20%) and inverter (-10% at -19%) peak torque, reduced the activation levels of the tibialis anterior (-11% at -13%) and peroneus longus (-18% at -24%) muscles, and increased vertical (+4% at +7%) and mediolateral (+5% at +27%) GRF. However, the ankle bracing allowed lower activation levels after the test for the peroneus longus (-11%) muscle, without causing any effect on inverter and evertor peak torque...